2020
DOI: 10.1158/2159-8290.cd-19-0116
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of HDAC3 Targets Synthetic Vulnerabilities and Activates Immune Surveillance in Lymphoma

Abstract: CREBBP mutations are highly recurrent in B-cell lymphomas and either inactivate its histone acetyltransferase (HAT) domain or truncate the protein. Herein, we show that these two classes of mutations yield different degrees of disruption of the epigenome, with HAT mutations being more severe and associated with inferior clinical outcome. Genes perturbed by CREBBP mutation are direct targets of the BCL6-HDAC3 onco-repressor complex. Accordingly, we show that HDAC3-selective inhibitors reverse CREBBP-mutant aber… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 49 publications
6
111
0
Order By: Relevance
“…These dysregulated pathways may be potential targets for improving the sensitivity to immunotherapy. Importantly, these results are in line with prior publications, which have provided some evidence that inhibition of epigenetic modification (Mondello et al, 2020) or activation of PPAR signaling pathways (Chowdhury et al, 2018;Saibil et al, 2019) might be a promising way to overcome therapeutic resistance to immune checkpoint blockade or ACT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These dysregulated pathways may be potential targets for improving the sensitivity to immunotherapy. Importantly, these results are in line with prior publications, which have provided some evidence that inhibition of epigenetic modification (Mondello et al, 2020) or activation of PPAR signaling pathways (Chowdhury et al, 2018;Saibil et al, 2019) might be a promising way to overcome therapeutic resistance to immune checkpoint blockade or ACT.…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Figure 6C, multiple epigenetic signaling pathways were upregulated in inflamed non-responders, which suggested a mechanism of immunotherapeutic resistance as observed by others (Mondello et al, 2020;Olino et al, 2020).…”
Section: Mechanistic Differences Between Inflamed Responsive Tme and supporting
confidence: 63%
“…It was reported that selective inhibition of HDAC3 could activate immune surveillance in lymphoma, resulting in the inhibition of lymphoma cell growth. 11 A clinical trial assessing the efficacy and safety of chidamide in patients with DLBCL in mainland China is currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…27 CREBBP mutations are associated with poor outcome in FL, 28 but KAT domain mutations are associated with a worse progression-free survival than nonsense/frameshift mutations. 11 Murine studies using Crebbp knockout (KO)/knockdown found that Crebbp loss promotes B-cell lymphoma in cooperation with Bcl2 overexpression 27,29,30 and that regions of reduced histone acetylation associated with Crebbp loss were primarily located at enhancer elements bound by BCL6. 29 Consistent with this, cKO of Crebbp in GCB cells leads to reduced expression of genes that are expressed in LZ GCB cells, such as those involved in antigen presentation on MHC class II, B-cell receptor signaling, and interferon signaling.…”
Section: Crebbp: Not All Mutations Are Created Equalmentioning
confidence: 99%
“…Key differences exist between the magnitudes of changes observed in mouse models using KO/knockdown versus primary tumors in which KAT domain mutations predominate 31 and when comparing patient outcomes by CREBBP mutational subtypes. Mondello et al 11 therefore investigated functional differences between CREBBP KAT domain mutations and nonsense/frameshift mutations. This was achieved using CRISPR/Cas9 gene editing to generate isogenic lymphoma cell lines with either wild-type CREBBP, CREBBP-R1446C mutation (a mutation hotspot in the KAT domain), or homozygous frameshift mutation (KO).…”
Section: Crebbp: Not All Mutations Are Created Equalmentioning
confidence: 99%